Metabolic deficiencies underlie reduced plasmacytoid dendritic cell IFN-I production following viral infection - Trever T. Greene; Yeara Jo; Carolina Chiale; Monica Macal; Ziyan Fang; Fawziyah S. Khatri; Alicia L. Codrington; Katelynn R. Kazane; Elizabeth Akbulut; Shobha Swaminathan; Yu Fujita; Patricia Fitzgerald-Bocarsly; et al. (Nature Communications)
Abstract Type I Interferons (IFN-I) are central to host protection against viral infections, with plasmacytoid dendritic cells (pDC) being the most significant source, yet pDCs lose their IFN-I production capacity following an initial burst of IFN-I, resulting in susceptibility to secondary infections. The underlying mechanisms of these dynamics are not well understood. Here we find that viral infection reduces the capacity of pDCs to engage both oxidative and glycolytic metabolism. Mechanistically, we identify lactate dehydrogenase B (LDHB) as a positive regulator of pDC IFN-I production in mice and humans; meanwhile, LDHB deficiency is associated with suppressed IFN-I production, pDC metabolic capacity, and viral control following infection. In addition, preservation of LDHB expression is sufficient to partially retain the function of otherwise exhausted pDCs, both in vitro and in vivo. Furthermore, restoring LDHB in vivo in pDCs from infected mice increases IFNAR-dependent, infection-associated pathology. Our work thus identifies a mechanism for balancing immunity and pathology during viral infections, while also providing insight into the highly preserved infection-driven pDC inhibition.